Printing in a pandemic: the makers response to COVID-19 (Journal of EAHIL, 2020)
uCreate Studio is the University of Edinburgh’s Community Makerspace. The uCreate Studio team worked throughout the COVID-19 lockdown, collaborating with other local teams to produce personal protective equipment (PPE) for staff in the National Health Service locally. This paper describes the work of the uCreate Studio team and how they used their skills, knowledge, network of contacts, and the specialist equipment in the uCreate Studio in the production of PPE.